An inhibitory glycinergic projection from the cochlear nucleus to the lateral superior olive - Weingarten, Dennis J.; Sebastian, Eva; Winkelhoff, Jennifer; Patschull-Keiner, Nadine; Fischer, Alexander U.; Wadle, Simon L.; Friauf, Eckhard; Hirtz, Jan J. (Frontiers in Neural Circuits, 2023)
Auditory brainstem neurons in the lateral superior olive (LSO) receive excitatory input from the ipsilateral cochlear nucleus (CN) and inhibitory transmission from the contralateral CN via the medial nucleus of the trapezoid body (MNTB). This circuit enables sound localization using interaural level differences. Early studies have observed an additional inhibitory input originating from the ipsilateral side. However, many of its details, such as its origin, remained elusive. Employing electrical and optical stimulation of afferents in acute mouse brainstem slices and anatomical tracing, we here describe a glycinergic projection to LSO principal neurons that originates from the ipsilateral CN. This inhibitory synaptic input likely mediates inhibitory sidebands of LSO neurons in response to acoustic stimulation.